2018
DOI: 10.1155/2018/1364186
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Drying and Wetting Cycles and Compaction Degree on Strength of Yudong Silt for Subgrade and Its Prediction

Abstract: In order to investigate the influences of drying and wetting cycles, initial degree of compaction, and water content on shear strength of the Yudong subgrade silt, a series of direct shear tests were performed at saturated and unsaturated states. The test results show that effects of the drying and wetting cycles, water content, and compaction degree on cohesion are more evident than those on the internal friction angle. According to the test data, a formula for the cohesion was proposed, which accounts for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Lime is a prevalent and effective additive that has been widely used for soil stabilization. Previous studies showed that lime addition can increase the optimum water contents, shrinkage limits, and strengths of the mixtures but decrease the liquid limits, plasticity indexes, and maximum dry densities of the mixtures [6][7][8][9][10][11][12][13]. However, in engineering practice, there are lots of environmental conditions which can affect the effect of chemical stabilization of soil foundations.…”
Section: Introductionmentioning
confidence: 99%
“…Lime is a prevalent and effective additive that has been widely used for soil stabilization. Previous studies showed that lime addition can increase the optimum water contents, shrinkage limits, and strengths of the mixtures but decrease the liquid limits, plasticity indexes, and maximum dry densities of the mixtures [6][7][8][9][10][11][12][13]. However, in engineering practice, there are lots of environmental conditions which can affect the effect of chemical stabilization of soil foundations.…”
Section: Introductionmentioning
confidence: 99%
“…Five soils including expansive soil (Zhang et al 2016) [12], silty soil (Zhang et al 2018) [13] and sandy soils (Wang et al 2017) [11] were chosen for the study considering the breadth of soil types. The particle size distribution curves of five soils are shown in Fig.…”
Section: Basic Properties Of the Five Soilsmentioning
confidence: 99%
“…Aldaood et al (2014) adding water from a burette and drying in air. Zhang et al (2018) performed direct shear tests on Silt subjected to cyclic submerging in water and drying in air. The existing research all indicates that dryingwetting cycles have negligible detrimental impacts on the mechanical properties of soil (Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%